2020
DOI: 10.1017/jfm.2020.747
|View full text |Cite
|
Sign up to set email alerts
|

Thermocapillary instabilities in a liquid layer subjected to an oblique temperature gradient

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 46 publications
6
41
0
Order By: Relevance
“…The stability of the linear and return flows was explored in detail by Smith & Davis (1983a,b). Furthermore, the thermocapillary instabilities arising due to an imposed OTG have been also investigated by Nepomnyashchy & Simanovskii (2004), Shklyaev & Nepomnyashchy (2004), Nepomnyashchy & Simanovskii (2009) and Patne, Agnon & Oron (2020b, 2021a. Shklyaev & Nepomnyashchy (2004) and Patne et al (2021a) revealed a strong stabilizing effect of the imposed HTG component on the instability triggered by the VTG component of the imposed OTG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of the linear and return flows was explored in detail by Smith & Davis (1983a,b). Furthermore, the thermocapillary instabilities arising due to an imposed OTG have been also investigated by Nepomnyashchy & Simanovskii (2004), Shklyaev & Nepomnyashchy (2004), Nepomnyashchy & Simanovskii (2009) and Patne, Agnon & Oron (2020b, 2021a. Shklyaev & Nepomnyashchy (2004) and Patne et al (2021a) revealed a strong stabilizing effect of the imposed HTG component on the instability triggered by the VTG component of the imposed OTG.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the thermocapillary instabilities arising due to an imposed OTG have been also investigated by Nepomnyashchy & Simanovskii (2004), Shklyaev & Nepomnyashchy (2004), Nepomnyashchy & Simanovskii (2009) and Patne, Agnon & Oron (2020b, 2021a. Shklyaev & Nepomnyashchy (2004) and Patne et al (2021a) revealed a strong stabilizing effect of the imposed HTG component on the instability triggered by the VTG component of the imposed OTG. Additionally, Patne et al (2021a) demonstrated the existence of an entirely new class of thermocapillary modes arising as a result of the interaction between the imposed HTG and VTG.…”
Section: Introductionmentioning
confidence: 99%
“…Further details of the discretisation of the governing equations and boundary conditions, and the construction of the matrices A and B, are presented in the standard procedure described by Trefethen (2000) and Schmid & Henningson (2001). Application of the pseudospectral method for similar problems can be found in Patne, Agnon & Oron (2020, 2021. We use the polyeig MATLAB routine to solve the generalised eigenvalue problem given by (3.4).…”
Section: Methodsmentioning
confidence: 99%
“…Marangoni convection in an infinite thin liquid layer (Birikh 1966; Smith & Davis 1983; Hu et al. 2017; Kowal, Davis & Voorhees 2018; Patne, Agnon & Oron 2021), a rectangular cavity (Strani, Piva & Graziani 1983; Shieh & Yang 1987; Peltier & Biringen 1993; Chen & Xu 2021), a two layer system (Doi & Koster 1993; Liu, Roux & Velarde 1998), a point-heating cavity (Hamed & Floryan 2000; Wei, Liu & Lin 2012), a cylindrical cavity (Kang et al. 2016), a liquid bridge (Kang et al.…”
Section: Introductionmentioning
confidence: 99%
“…2018) with an oblique temperature gradient (Patne, Agnon & Oron 2020; Patne et al. 2021) or with phase change (Shmyrov et al. 2019; Salgado Sánchez et al.…”
Section: Introductionmentioning
confidence: 99%